Psychological pressure among university professors according to some demographic variables at the University of Amar Thelidji Laghouat - Ayate , Amine; Boufatah , Mohamed (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The study aimed to identify the psychological pressures of university professors and the differences in them according to some demographic variables (gender, age, experience). In order to achieve the goals of the study, a tool was built to measure psychological stress, which consisted of (68) items distributed across ten dimensions. The validity and reliability of the tool were verified. The study sample included (117) university professors from the University of Ammar Thaliji in Laghouat, Algeria. The results indicated that there were no differences between the teachers in the psychological pressures, regardless of the type of demographic variables (gender, age, experience (. Teachers suffer from moderately severe psychological stress, in other words, the study sample members are exposed to psychological pressures associated with the sources studied, so we suggest: - Attention to the university professor in terms of material, residential, social and strategic. - Conduct studies to find out the mechanisms and strategies by which the university professor resists psychological stress.